Optimizing the geometric programming problem with single-term exponents subject to max–min fuzzy relational equation constraints - Wu, Yan-Kuen (Mathematical and computer modelling, 2008)
In this study we investigate the problem of minimizing an objective function with single-term exponents subject to fuzzy relational equations specified in max–min composition. Two folds are presented. First, we present some properties for this optimization problem under the assumption of both negative and nonnegative exponents in the objective function. Second, we provide an efficient procedure to solve this optimization problem without looking for all the potential minimal solutions. Two concrete examples are provided to illustrate the procedure.